Neuropeptides in atopic dermatitis (Faculty of Medicine Universitas Indonesia, 2001)
The nervous system, the immune system, and the cutaneous system are not independent systems, but are closely associated and use the same language of cytokines and neurotransmitters. Atopic dermatitis (AD) is exacerbated by several factors, such as emotional stress, scratching and sweating. This review presents the role of neuropeptides (NP) in AD. In AD, abnormalities occur in distribution of some types of neural filaments and in the associated active NP. Nerve fibre increases. Nerve fibres for substance-P (SP) and calcitonin gene-related peptide (CGRP) are positive, The cutaneous concentration of SP decreases while vasoactive-intestinal polypeptide (VIP) increases. Immunohistochemical examination has revealed neuropeptide-Y (NPY)-positive dendritic epidermal cells in AD lesions but no somatostatin (SOM) fibres. Neuromediators modulate functions of all cutaneous cellular types, which are all part of the neuroimmunocutaneous system (NCIS): endothelial cells, glandular cells, fibroblasts, epidermal cells and immune cells. Conclusion: during the course of AD, the NICS is destabilized. Evidence show that NP can also be responsible for the induction and maintenance of the cutaneous inflammation process and confirm an involvement in the pathogenesis of AD. Release of the NP by cutaneous nerve potentially explains the role of emotional stress, scratching and sweating in exacerbation of AD. (Med J Indones 2001; 10: 197-200)